77: Reduction of Noise in the Neonatal Intensive Care Unit Using Sound-Activated Noise Alarms. Issue 6 (1st June 2014) - Wang, D; Aubertin, C; Barrowman, N; Moreau, K; Dunn, S; Harrold, J
Abstract: BACKGROUND: Sound levels in neonatal intensive care units (NICU) often exceed recommendations. An adverse sound environment may have harmful effects on newborns. Previous studies have explored strategies to reduce sound levels in the NICU but few have focused on direct audit and feedback methods. OBJECTIVES: To determine if the use of noise alarms, providing direct audit and feedback, reduces sound levels in a level 3 NICU. DESIGN/METHODS: SoundEar® noise alarms were installed in each of three patient care areas (blue, yellow and green pod) and at a central desk area in a level 3 NICU. The alarms continuous measured sound levels and provided direct audit and feedback. Above a set threshold the alarm displayed red, within 5 dB the alarm displayed yellow and at more than five dB below threshold the alarms displayed green. Sound levels were measured for two months with the noise alarms visible but not providing any direct audit and feedback (i.e. always displaying red). The threshold was then set to 50 dB, a level which (based on previous data) could discriminate quiet from noisy periods in our NICU. Sound data was collected for another two months. Data was adjusted for measures of unit activity. The adjusted sound levels pre and post direct audit and feedback were compared. RESULTS: The percent of measured sound levels below 45 dB, 50 dB and 55 dB post intervention and the difference from pre-intervention are shown below in Table 1 . The largest effect was a statistically significant increase in the percentage of sound levels below 50 dB in all three patient care areas. The desk area did not show a change. The percentage of time where sound levels were below 45 dB and 55 dB was also not significantly altered by direct audit and feedback. CONCLUSIONS: Noise alarms providing direct audit and feedback seem effective in reducing sound levels in patient care areas. Conversations may have moved to non-patient care areas, preventing a similar change there. The time below 45 dB did not change likely due to non-modifiable background noise levels. The lack of effect for 55 dB is possibly due to the unit being below this threshold the majority of the time pre-intervention.